Catechin-Rich Green Tea Extract Reduced Intestinal Inflammation and Fasting Glucose in Metabolic Syndrome and Healthy Adults: A Randomized, Controlled, Crossover Trial. (14th June 2022) - Hodges, Joanna; Zeng, Min; Cao, Sisi; Pokala, Avinash; Rezaei, Shahabbedin; Sasaki, Geoffrey; Vodovotz, Yael; Bruno, Richard
Abstract: Objectives: Preclinical evidence demonstrated that catechin-rich green tea extract (GTE) improves gut barrier function and reduces intestinal and systemic inflammation. Thus, this clinical trial was conducted to test the hypothesis that GTE would alleviate intestinal inflammation relative to cardiometabolic risk in persons with metabolic syndrome (MetS). Methods: We conducted a randomized, double-blind, placebo-controlled, crossover trial in adults with MetS and age- and gender-matched healthy persons who received confections without (placebo) or with 1 g/d GTE (890 mg catechins) for 28 d while following a low-polyphenol diet. Dietary polyphenols, fasting blood glucose, insulin, and lipids were assessed at d 0, 14, and 28 of each intervention. Intestinal inflammation was assessed by measuring neutrophil-derived calprotectin and myeloperoxidase by ELISA in pooled stool samples collected over the last 3 d of each intervention. Data were analyzed using RM ANOVA and multiple linear regression. Results: MetS (n = 21; 40 ± 3 y; 35 ± 1 kg/m 2 ) and healthy (n = 19; 34 ± 2 y; 22 ± 0.4 kg/m 2 ) persons completed the study with high compliance (>95%), no adverse effects, or changes in body mass. Participants' total polyphenol intakes decreased during each intervention compared with baseline (P < 0.001). Fecal calprotectin and myeloperoxidase were lower (P < 0.05) in GTE compared with placebo regardless of health status. Although fasting insulin, triglycerides, total and high-density lipoprotein cholesterol were unaffected by treatment, fasting glucose decreased (P < 0.01) in response to GTE regardless of health status. Age (β = −0.29; P = 0.05) and between-trial changes in myeloperoxidase (β = 0.03; P < 0.04) were predictive of changes in insulin after controlling for sex, waist circumference, and changes in blood lipids and calprotectin. Conclusions: Dietary intervention with GTE-rich confections in weight-stable healthy and MetS adults decreased fasting glucose and intestinal inflammation, which was associated with improvements in fasting insulin. This suggests that gut-level anti-inflammatory activities of GTE may improve glycemic control with reductions in intestinal inflammation contributing to enhance insulin sensitivity. Funding Sources: USDA-NIFA, USDA-HATCH, and the Ohio Agricultural Research and Development Center at the Ohio State University.